Europäische Verteidigung Von der EVG zur Europäischen Armee? Analyse und Modell aus europa- und verfassungsrechtlicher Perspektive - Scheffel, Nikolaus (Mohr Siebeck, 2022)
How could the idea of joint European armed forces be realised? Nikolaus Scheffel analyses the historical model of the European Defence Community from the 1950s and contrasts it with the institutional network of the Common Security and Defence Policy that exists today. He critically examines the case law of the Federal Constitutional Court before proposing a model that would be democratically legitimised through a Europeanised parliamentary reservation.
PublicationDate: 20220830
Keywords: europäische Integration -- Friedenssicherung -- Streitkräfte -- Parlamentsvorbehalt -- Europäische Verteidigungsgemeinschaft -- tax -- EVG -- Völkergewohnheitsrecht -- Verbundsarmee -- Angriffskrieg -- GSVP -- Robert-Koch-Institut -- Verfassungsrecht und Staatslehre -- Völkerrecht -- Europarecht